EFEK MEDIASI PROFITABILITAS: PADA ANALISIS PENGARUH KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN ERA PANDEMI COVID-19 - Hairudin Hairudin; Rini Loliyani; Rina Loliyana (LP2M Universitas Bina Bangsa, 2022)
This study aims to determine the effect of investment decisions proxied by total assets growth (TAG) on the value of companies proxiedwith price to book value (PBV) with profitability proxied by return on assets (ROA) as an intervening variable in mining sector companies listed on the Indonesia Stock Exchange for the 201 6-20 period 20. The population and samples used in this study were 26 balanced sector companies that had complete financial statements and were listed on the Indonesia Stock Exchange for the period 201 6-2020. The data analysis method used in this study is Path Analysis. The results of this study show that: 1) Investment decisions (TAG) have a positive and significant influence on company value (PBV): 2) Investment decisions (TAG) have a positive and significant influence on profitability (ROA): 3) Profitability has a positive and significant effect on company value: 4) Profitability is able to mediate the influence of investment decisions (TAG) on company value (PBV) in mining sector companies on the Indonesia Stock Exchange for the 2016-2020 period during the Covid-19 pandemic era